Recreated Subjects, Reconstructed Copies: Considerations on the Photographic Process - Petri, Grischka (Venezia Arti, 2021)
This article considers the dichotomy of originals and copies in the specific context of photographs of objects that recreate an existing work of art or a documentary photograph. The examples span the period from the mid-nineteenth century to contemporary photographic practices. The traditional legal regulation of such copies is unsatisfactory compared with more recent theoretical approaches, as those proposed here. These approaches encompass the two modes of photographic copies after recreated realities: they simultaneously preserve identities and create original alterations.